The effect of young papaya abon on breast milk expenditures of postpartum mothers 3–7 day - Cahyati, Nanik; Waslia, Dede; Herawati, Nia (MEDIA ILMU KESEHATAN, 2025)
Background: The number of breastfeeding problems in early postpartum, one of which is not smooth breast milk, results in low exclusive breastfeeding coverage in West Bandung Regency in 2021 which is 72.76%, Rongga Health Center January - May 2023 only 29%. One of the efforts to increase breast milk production by consuming young papaya fruit, processed into abon because it is much favored by all circles of society.Objective: The purpose of the study was to determine the effect of young papaya abon on breast milk production of postpartum women on days 3-7, in the working area of the Rongga Health Center, West Bandung Regency.Methods: Quantitative method and quasi experiment design of one group pre and posttest, population of 90 postpartum women, 20 samples of postpartum women on days 3-7 with quota sampling technique. Data collection with observation sheet instruments, SOP and Wilcoxon test.Results: Statistical test results mean before intervention 2.20, mean after intervention 7.50 with p-value=0.0001 (α<0.05).Conclusion: It is concluded that there is an effect of giving shredded young papaya on breast milk production of postpartum women on days 3–7. It is recommended that midwives provide care during the lactogenesis period in order to achieve successful breastfeeding and make innovations that can increase exclusive breastfeeding coverage.